Development of Optimal Tour Time Model for Tourist Destinations in A City: Application in Pokhara City Network - Baral, Purushottam; Shrestha, Jagat Kumar (Technical Journal, 2019)
When a tourist visits a city, they tend to visit as many touristic places in the city as possible within their time limit. So, for optimization of their limited time budget and allowing them to spend their maximum time in the destination, this paper proposes a model to find an optimal route for the destination points a tourist is interested into. The computer model developed in this paper makes a sub-tour within the original network and search for an optimal tour route hence giving total travel time and total time required to visit desired destinations, and returning back to the place where you started from. The model enables fast decision support for tourists. The model developed is then applied in network of Pokhara and optimal route is found for a sample set of destinations.